MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI MENULIS PANTUN KELAS 5 SD NEGERI 004 TEBING TINGGI MENGGUNAKAN METODE MODELLING THE WAY BERBANTU MEDIA AUDIO VISUAL - Haspi Delnis (PGRI Provinsi Riau, 2021)
This study aims to improve student learning outcomes by using the application of the method of modeling the way through audio-visual media for class V at SD Negeri 004 Tebing Tinggi. The research was carried out in two cycles on 20 students. In pre-cycle learning, the average result of the students is 62.56, there are 9 students who reach the KKM or 45%. The results of teacher observations of students who can answer the teacher's questions are only 9 students, or 45%. Cycle 1 obtained an average score of 78.65 which reached the KKM of 14 people or 70%. Based on the teacher's observation data on students who can answer questions, there are 14 students or 70%. Cycle 2 obtained an average score of 86.30 and all students have reached the KKM. Based on the teacher's observations of 20 students in cycle 2, all of them could answer well and correctly, and had reached the KKM 100%. The application of the modeling the way method through audio-visual media has had a very good influence on students in improving learning outcomes, and motivating students in the teaching and learning process in the classroom to be more enthusiastic, lively and confident. So that the material presented by the teacher can be easily understood and understood by students. The responsibility of students towards assignments is high, as well as helping students to be actively involved in the classroom and be more creative in expressing ideas in the words of writing Pantun.